Isolation, Screening and Production of Biosurfactant by Bacillus clausii 5B - A, Aparna; Srinikethan, G.; Hegde, Smitha (Research in Biotechnology, 2012)
Primary somatic embryos induced from the callus tissues revealed the presence of CSSV between 12-24 wks by PCR/capillary electrophoresis while PCR/agarose electrophoresis failed to detect the virus. Different carbon and nitrogen sources were evaluated for their effect on biosurfactant production. Maximum biosurfactant synthesis (2.11 g/L) was observed at 96 hours when the cells were grown on minimal medium containing 1 % (w/v) glucose as carbon source. Among nitrogen sources tested, ammonium chloride showed maximum biosurfactant production of 2.41 g/L. The biosurfactant produced by the bacterial isolate reduced the surface tension of the cell free broth from 53.56 mN/m to 29.48 mN/m. Compositional analysis of the biosurfactant revealed that it was of lipopetide type, composed of high percentage of lipid (~56 %, w/w) and protein (~39 %, w/w) content.